Breast feeding and immunoprophylaxis efficacy of mother-to-child transmission of hepatitis B virus. (January 2014) - Zhang, Lei; Gui, Xien; Fan, Jingyi; Wang, Bo; Ji, Huiping; Yisilafu, Reziyan; Li, Fengliang; Zhou, Yun; Tong, Yan; Kong, Xiaoling; Ye, Ping; Zong, Lili
Abstract Objective: This study was designed to explore if hepatitis B virus (HBV) may be transmitted via breast milk through mother-to-child transmission (MTCT), and assay the immunoprophylaxis efficacy after passive–active immunization. Method: From year 2008 to 2012, 67 720 pregnant women were screened and 1186 HBsAg-carrier mothers and their infants aged 8–12 months were followed in multi-centers of China, among whom HBV markers (HBsAg, HBsAb, HBeAg, HBeAb and HBcAb) and HBV-DNA were measured. Results: HBsAg positive rate of pregnant women was 6.7% (4533/67 720) and infants' immunoprophylaxis failure rate was 3.3% (39/1186). Immunoprophylaxis failure infants were all born to mothers of HBeAg positive and HBV-DNA >6 log10 copies/ml. Among infants of HBeAg positive mothers, HBV infection rate was 9.0% and HBsAg positive rate was 8.3% in breast-feeding group versus 9.2% in formula-feeding group, P = 0.761. Occurrence of perinatal HBV infection was indicated in uterus or during delivery. Different feeding patterns had no effects on HBsAb conversion of infants with the implementation of immunization. Conclusions: HBsAg prevelance rate of pregnant women enrolled was 6.7% and immunoprophylaxis failure rate of infants was 3.3%, while the infection rate reached 9.0% in infants of HBeAg positive mothers. Breast feeding did not increase the occurrence of HBV MTCT.